Crystal Structures of Compounds Containing Ions Selenite - Claudia Graiff (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The chemistry of materials containing Se oxyanions in the +4 oxidation state, such as selenite, hydrogenselenite, and oxoselenate, are of increasing interest in the research community for several reasons. First, the lone pair on the selenium atom can behave as structure-directing agent towards the formation of materials characterized by the presence of hollows or channels in their intimate structures, moreover, the weakly coordinative capability of the Se(IV) electron lone pairs could give rise to interesting supramolecular interactions, and finally, it is known that the incorporation of selenite anions can lead to non-centrosymmetric structures and, consequently, to materials displaying remarkable physicochemical properties. The most important feature is that the full comprehension of the properties of this type of materials cannot be exhaustively understood unless the complete solid state crystal structure is available. In this Special Issue, entitled "Crystal Structures of Compounds Containing Ions Selenite", a series of new selenite-containing compounds synthesized by different methodologies and fully caracterized in the solid state is reported. Moreover the fundamental role of detailed structural analysis in understanding the interactions in the solid state that are responsible for the peculiar chemical-physical properties of such materials is discussed.